2012
DOI: 10.1021/mp300316n
|View full text |Cite
|
Sign up to set email alerts
|

Interleukin-10: An Anti-Inflammatory Marker To Target Atherosclerotic Lesions via PEGylated Liposomes

Abstract: Atherosclerosis (AS) causes cardiovascular disease, which leads to fatal clinical end points like myocardial infarction or stroke, the most prevalent causes of death in developed countries. An early, noninvasive method of detection and diagnosis of atherosclerotic lesions is necessary to prevent and treat these clinical end points. Working toward this goal, we examined recombinant interleukin-10 (IL-10), stealth liposomes with nanocargo potency for NMRI relevant contrast agents, and IL-10 coupled to stealth li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
45
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 56 publications
(45 citation statements)
references
References 53 publications
0
45
0
Order By: Relevance
“…Also, it is well known that macrophages are predisposed to phagocytize particles such as liposomes (16,17), and several liposome-based imaging probes have been reported recently (27,28). Therefore, in this study, we used liposomes as carriers for the atherosclerotic region and designed a SPECT imaging probe.…”
Section: Discussionmentioning
confidence: 99%
“…Also, it is well known that macrophages are predisposed to phagocytize particles such as liposomes (16,17), and several liposome-based imaging probes have been reported recently (27,28). Therefore, in this study, we used liposomes as carriers for the atherosclerotic region and designed a SPECT imaging probe.…”
Section: Discussionmentioning
confidence: 99%
“…We have previously shown that Atto655-IL10 penetrates deep into the plaques when liposomes were the nanocarrier 12 (see also in Figure 5A and B). Upon switching the NP to IL10-coated proticles and comparing all formulations, we observed a different staining pattern where the signal originated more on the surface of the atherosclerotic-plaques ( Figure 5C) and strongly co-localized with the endothelium ( Figure 2D) and partially with CD68-positive macrophages on the plaque surface ( Figure 3D).…”
mentioning
confidence: 69%
“…8 It plays a key role in counter-regulating the immune and inflammatory responses in AS pathogenesis by inhibiting the production of pro-inflammatory cytokines and mediators from macrophages and dendritic cells. [9][10][11][12] The comparatively high amounts of IL10 found in atherosclerotic-plaques make it diagnostically relevant. 13,14 IL10 is produced by a variety of sources which include, but are not limited to, T-helper cells, 15 monocytes, macrophages, 9 epithelial cells, and tumor cells.…”
Section: Introductionmentioning
confidence: 99%
“…Although nanoparticle-based therapy is becoming more and more common in oncology, no specific nanoparticle-based system has yet been approved for diagnosis or therapy in cardiovascular diseases (8)(9)(10)(11)(12). Indeed, integrating a transport mechanism, a stealth coating, targeting and an active molecule into one and the same nanosystem (known as a third-generation nanosystem) has not yet been clinically validated in the field of atherosclerosis.…”
Section: Nanoathero: On the Way To Circumvent Challenges In Atherothrmentioning
confidence: 99%